China's Emerging National Security Interests and Their Impact on the People's Liberation Army - Scot Tanner, Murray (Marine Corps University Press (MCUP), 2015)
As China's security interests expand and its power grows, it may increasingly have to choose between a long-range calculation that it should avoid angering its neighbors in the region and a short-term desire to display its newly won capacity to defend its interests and assert its power. Drawing on our analysis, we see themes that indicate growing support for China to pursue what we might call "defensive expansion" of China's presence and influence in Asia, including its military presence and influence. Underlying this support for defensive expansion we see three themes recurring throughout China's debates over its emerging interests. First, that China's security community sees its emerging xii | Introduction Introduction | xiii national security interests as increasingly indispensable to China's future development and power. Second, that China sees many of these interests as increasingly vulnerable or at risk from both traditional and nontraditional threats. And third, that China portrays itself as having exercised much greater restraint in asserting and protecting its interests than many of its neighbors.